Sustainable Capital Budgeting: Assessing Long-Term Effects Beyond Profitability - Nurfitriani Nurfitriani; Imam Nazarudin Latif (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: This research seeks to create and implement a multidimensional scoring mechanism for assessing sustainability initiatives across several sectors. The research aims to transcend conventional financial measurements by incorporating economic, environmental, social, and governance (EESG) factors, thereby providing a more comprehensive framework for project evaluation. Method: This study employs a literature-based conceptual framework and a composite indicator methodology to create weighted score matrices for three separate case studies: a carbon retrofit program, a regional water infrastructure enhancement, and a circular packaging business. Each case is assessed using twelve indicators and displayed on radar charts to show performance profiles and strategic trade-offs. Findings: The results indicate that each project excels in different areas, highlighting the need for evaluations to consider the situation. The carbon retrofit argument is strong in terms of the environment and governance, while the water infrastructure project is balanced and has a big social impact. The circular packaging project earns high marks for environmental innovation and community engagement, despite not generating as much revenue. Radar charts are a good way to show these profiles, which helps with clear decision-making and comparing different sectors. Novelty/Value: This study advances theory by transforming EESG dimensions into a versatile, reproducible framework. In practice, it provides individuals involved in sustainability planning, investing, and policymaking with a tool to aid their decision-making. The model can be applied across various industries and locations, making it a versatile tool for open evaluation that focuses on driving positive change in line with global sustainability goals.